Nuclear dependence of light neutral meson production in p-A collisions at 400 GeV with NA60 - Arnaldi, Roberta; Banicz, Karoly; Damjanović, Sanja; Specht, Hans Joachim (The European physical journal. C, Particles and fields, 2019)
The NA60 experiment has studied low-mass muon pair production in proton-nucleus collisions with a system of Be, Cu, In, W, Pb and U targets, using a 400 GeV proton beam at the CERN SPS. The transverse momentum spectra of the ρ/ωρ/ω\rho /\omega and ϕϕ\phi mesons are measured in the full pTpTp_{\mathrm {T}} range accessible, from pT=0pT=0p_{\mathrm {T}}= 0 up to 2GeV/c2GeV/c2 \, {\hbox {GeV/c}}. The nuclear dependence of the production cross sections of the ηη\eta , ωω\omega and ϕϕ\phi mesons has been found to be consistent with the power law σpA∝AασpA∝Aα\sigma _{\mathrm {pA}} \propto {\mathrm {A}}^\alpha , with the αα\alpha parameter increasing as a function of pTpTp_{\mathrm {T}} for all the particles, and an approximate hierarchy αη≈αϕ>αωαη≈αϕ>αω\alpha _\eta \approx \alpha _\phi > \alpha _\omega . The cross section ratios ση/σωση/σω\sigma _\eta /\sigma _\omega , σρ/σωσρ/σω\sigma _\rho /\sigma _\omega and σϕ/σωσϕ/σω\sigma _\phi /\sigma _\omega have been studied as a function of the size A of the production target, and an increase of the ηη\eta and ϕϕ\phi yields relative to the ωω\omega is observed from p-Be to p-U collisions.